The Winchcombe meteorite, a unique and pristine witness from the outer solar system - King, A.J.; Daly, L.; Rowe, J.; Joy, K.H.; Greenwood, R.C.; Devillepoix, Hadrien; Suttle, M.D.; Chan, Q.H.S.; Russell, S.S.; Bates, H.C.; Bryson, J.F.J.; Clay, P.L.; et al. (2022)
Direct links between carbonaceous chondrites and their parent bodies in the solar system are rare. The Winchcombe meteorite is the most accurately recorded carbonaceous chondrite fall. Its pre-atmospheric orbit and cosmic-ray exposure age confirm that it arrived on Earth shortly after ejection from a primitive asteroid. Recovered only hours after falling, the composition of the Winchcombe meteorite is largely unmodified by the terrestrial environment. It contains abundant hydrated silicates formed during fluid-rock reactions, and carbon- and nitrogen-bearing organic matter including soluble protein amino acids. The near-pristine hydrogen isotopic composition of the Winchcombe meteorite is comparable to the terrestrial hydrosphere, providing further evidence that volatile-rich carbonaceous asteroids played an important role in the origin of Earth’s water.